An apostle in battle: Paul and spiritual warfare in 2 Corinthians 12:1-10 - Bowens, Lisa M. (Wissenschaftliche Untersuchungen zum Neuen Testament, 2017)
Cover -- Preface -- Table of Contents -- List of Abbreviations -- Chapter 1: Introduction -- 1.1 Proem -- 1.2 Snapshot of 2 Corinthians 12:1-10 and Its Context -- 1.3 Paul's Himmelsreise in Recent Interpretations -- 1.3.1 Garland, Murphy O'Connor, and Schweitzer -- 1.3.2 Baur, Plummer, and Windisch -- 1.3.3 Schmithals and Reitzenstein -- 1.3.4 Käsemann and Betz -- 1.3.5 Lincoln and Tabor -- 1.3.6 Gooder and Wallace -- 1.4 An Epigrammatic Survey of Early Christian Interpreters -- 1.4.1 Paul's Ascent in the Writings of the Church Fathers -- 1.4.2 Cosmological Affinities Between Paul and the Early Church Fathers -- 1.5 Argument of this Study -- 1.5.1 A Fresh Approach: Paul's Cosmic Battle Imagery -- 1.5.2 Definition of Terms -- 1.5.2.1 Cosmic, Cosmological, and Apocalyptic -- 1.5.2.2 Epistemology and Theological Anthropology -- 1.5.3 Methodology -- 1.5.3.1 A Word Regarding Paul's Opponents -- 1.6 Summary -- Chapter 2: Paul's Cultural Encyclopedia: Martial Language and the Cosmological, Epistemological, and Anthropological Nexus -- 2.1 Introduction -- 2.2 Prelude to War: The Apostle's Appeal to the Meekness and Gentleness of Christ (10:1-2) -- 2.3 The Significance of the Military Imagery -- 2.3.1 Paul's Use of κατὰ σάρκα in 2 Corinthians -- 2.3.2 Paul's Military Language in 10-13 -- 2.3.3 Summary of Military Imagery -- 2.4 Arena of Warfare: The Mind and Knowledge of God 10:4-6 -- 2.4.1 Noēma (Νόημα) -- 2.4.2 Additional Epistemological Terms in 2 Corinthians 10-13 -- 2.4.3 Paul's Use of Genesis 1-3 and Traditions Surrounding Genesis 1-3 -- 2.5 The War Scroll -- 2.6 1QS Treatise of the Two Spirits 3.13-4.26 -- 2.7 Excursus: An Additional Word on the War Scroll, The Treatise of the Two Spirits, and Paul -- 2.8 1QHᵃ and the Aramaic Levi Document -- 2.8.1 Community Hymns -- 2.8.2 The Aramaic Levi Document.